Application of 3D Rapid Prototyping Technology in Posterior Corrective Surgery for Lenke 1 Adolescent Idiopathic Scoliosis Patients - Yang, Mingyuan; Li, Chao; Li, Yanming; Zhao, Yingchuan; Wei, Xianzhao; Zhang, Guoyou; Fan, Jianping; Ni, Haijian; Chen, Ziqiang; Bai, Yushu; Li, Ming (Medicine (Baltimore), 2015)
A retrospective study to evaluate the effectiveness of 3-dimensional rapid prototyping (3DRP) technology in corrective surgery for Lenke 1 adolescent idiopathic scoliosis (AIS) patients. 3DRP technology has been widely used in medical field; however, no study has been performed on the effectiveness of 3DRP technology in corrective surgery for Lenke 1 AIS patients. Lenke 1 AIS patients who were preparing to undergo posterior corrective surgery from a single center between January 2010 and January 2012 were included in this analysis. Patients were divided into 2 groups. In group A, 3-dimensional (3D) printing technology was used to create subject-specific spine models in the preoperative planning process. Group B underwent posterior corrective surgery as usual (by free hand without image guidance). Perioperative and postoperative clinical outcomes were compared between 2 groups, including operation time, perioperative blood loss, transfusion volume, postoperative hemoglobin (Hb), postoperative complications, and length of hospital stay. Radiological outcomes were also compared, including the assessment of screw placement, postoperative Cobb angle, coronal balance, sagittal vertical axis, thoracic kyphosis, and lumbar lordosis. Subgroup was also performed according to the preoperative Cobb angle: mean Cobb angle <50° and mean Cobb angle >50°. Besides, economic evaluation was also compared between 2 groups. A total of 126 patients were included in this study (group A, 50 and group B, 76). Group A had significantly shorter operation time, significantly less blood loss and transfusion volume, and higher postoperative Hb (all, P < 0.001). However, no significant differences were observed in complication rate, length of hospital stay, and postoperative radiological outcomes between 2 groups (all, P>0.05). There was also no significant difference in misplacement of screws in total populations (16.90% vs 18.82%, P = 0.305), whereas a low misplacement rate of pedicle screws was observed in patients whose mean Cobb angle was >50° (9.15% vs 13.03%, P = 0.02). Besides, using 3DRP increased the economic burden of patients (157,000 ± 9948.85 Ren Min Bi (RMB) vs 152,500 ± 11,445.52 RMB, P = 0.03). Using the 3D printing technology before posterior corrective surgery might reduce the operation time, perioperative blood loss, and transfusion volume. There did not appear to be a benefit to using this technology with respect to complication rate and postoperative radiological outcomes; however, 3D technology could reduce the misplacement rate in patients whose preoperative mean Cobb angle was >50°. Besides, it also increased the patients' hospital cost. Therefore, future prospective studies are needed to elucidate the efficacy of this emerging technology.